Work-family conflict among junior physicians : its mediating role in the relationship between role overload and emotional exhaustion. - Ahmad, Aminah (2010)
The use of a mediation model for understanding the mediating impact of work-family conflict on the relationship between role overload and emotional exhaustion has not been given much attention. Approach: This study tested a mediation model consisting of emotional exhaustion as the dependent variable and role overload as the independent variable, with work-family conflict as its mediator. Data were gathered from a sample of 220 female junior physicians aged 40 years and below, having at least one child as well as working full-time in 14 public hospitals in Malaysia, using self-administered questionnaires. The data were analyzed using correlation and multiple regression analyses. Results: Results of correlation analyses revealed that role overload was significantly related to work-family conflict and emotional exhaustion and work-family conflict was significantly related to emotional exhaustion. Results of a series of multiple regression analyzed indicated that work-family conflict partially mediated the relationship between role overload and emotional exhaustion. Conclusion/ Recommendations: Junior physicians who experience role overload seem to be more emotionally drained and seem to experience greater conflict between work and family roles. There is a need to reduce the role overload that physicians experience by reviewing the ratio between physicians and patients and re-assessing the number of work hours and the weekly frequency of on-calls. Limiting on-call frequency and hours may be more likely to reduce work-family conflict as well as emotional exhaustion.